The Effect of Medicaid on Dental Care of Poor Adults: Evidence from the Oregon Health Insurance Experiment. (8th September 2017) - Baicker, Katherine; Allen, Heidi L.; Wright, Bill J.; Taubman, Sarah L.; Finkelstein, Amy N.
Abstract : Objective: To evaluate the effect of Medicaid coverage on dental care outcomes, a major health concern for low‐income populations. Data Sources: Primary and secondary data on health care use and outcomes for participants in Oregon's 2008 Medicaid lottery. Study Design: We used the lottery's random selection to gauge the causal effects of Medicaid on dental care needs, medication, and emergency department visits for dental care. Data Collection: Data were collected for lottery participants over 2 years, including mail surveys ( N  = 23, 777) and in‐person questionnaires ( N  = 12, 229). Emergency department (ED) records were matched to lottery participants in Portland ( N  = 24, 646). Principal Findings: Medicaid coverage significantly reduced the share of respondents who reported needing dental care (−9.8 percentage points, p  < .001) or having unmet dental care needs (−13.5 percentage points, p  < 0.001). Medicaid doubled the share visiting the ED for dental care (+2.6 percentage points, p  = .003) and the use of anti‐infective medications often prescribed for dental care, but it had no detectable effect on uncovered dental care or out‐of‐pocket spending. Conclusions: Expansion of Medicaid covering emergency dental care substantially reduced unmet need for dental care, increasing ED dental visits and medication use, while not changing patient use of uncovered dental services.